2021
DOI: 10.1155/2021/3047437
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Exercise or Dietotherapy Is Not Better than Returning to a Regular Diet to Rebuild Lipid Homeostasis of Rats

Abstract: Our aim was to explore the effects of dietary and behavior interventions on lipometabolism caused by an unhealthy high-fat diet and the best method to rebuild lipid homeostasis of this lifestyle. Apart from normal diet rats, 34 rats were fed with high-fat emulsion for 4 weeks and then intervened for another 4 weeks. Eight of them were classified into high-fat control group, and 9 were sorted into high-fat diet with rice vinegar group. Meanwhile, 10 were put into high-fat diet in swimming group, and 7 were just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Regular exercise for 30 minutes 3-4 times a week is highly recommended to lower blood pressure and can increase HDL levels which can reduce the formation of atherosclerosis due to hypertension (Liu et al, 2018;Xia et al, 2022;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Regular exercise for 30 minutes 3-4 times a week is highly recommended to lower blood pressure and can increase HDL levels which can reduce the formation of atherosclerosis due to hypertension (Liu et al, 2018;Xia et al, 2022;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%